Get streaming! : quick steps to delivering audio and video online - Follansbee, Joe (Elsevier : Focal Press, 2004)
"Streaming your audio and video online is inexpensive, easy, and fun. Get the fast results you need with Get Streaming! - a step-by-step, introductory level book that gets you up and running today."--Jacket.